Empowerment from Within: A Grounded Theory of the Minangkabau Community-Based Empowerment Model Through the Kaum System - Muhamad Jamil; Muhamad Rudi Wijaya; Anas Habibi Ritonga; Azhar Jaafar (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2025)
This study examines the Kaum system as an indigenous model of community empowerment within Minangkabau society, focusing on Nagari Tabek Patah, West Sumatra. Addressing the limitations of dominant Western-centric empowerment frameworks, this research employs a grounded theory approach to explore how locally rooted social structures and cultural values foster sustainable empowerment mechanisms. Data were collected through participant observation, in-depth interviews with key customary leaders (Ninik Mamak), and document analysis. The findings reveal a cyclical four-stage empowerment model embedded within Minangkabau local wisdom: tahu di nan ampek (awareness), sauak aie mandikan diri (internalization), karajo ba pokok (actualization), and ingek jo jago (social control). These stages demonstrate how empowerment organically emerges through the integration of reason, religion, nature, and custom; is internalized within communal social spaces; is actualized through participatory practices such as deliberation and mutual cooperation; and is sustained by community-based social control mechanisms grounded in customary law. The study demonstrates that empowerment within the Kaum system is not merely economic or externally driven but is deeply rooted in cultural identity, social capital, and collective agency. By situating local Minangkabau perspectives in dialogue with global theories such as Freire’s critical consciousness, Bourdieu’s habitus, and Sen’s capability approach, this research contributes to the broader discourse on community empowerment. It underscores the importance of culturally grounded, participatory, and sustainable development models, offering an alternative framework for understanding empowerment in non-Western and indigenous contexts.